Pengaruh Tingkat Bagi Hasil, Financing to Deposit Ratio (FDR) Dan Tingkat Inflasi Terhadap Deposito Mudharabah Pada Bank Umum Syariah (BUS) Periode 2014 – 2017 - Firda Izzati Febriani (Universitas Muhammadiyah Malang, 2019)
This study aims to determine the factors affect the amount of mudharaba deposits in Sharia Commercial Banks period 2014-2017. Factors affecting mudharaba deposits are used in this study which profit sharing rate, liquidity level measured by financing to deposit ratio, and inflation rate. The method used in this research is quantitative descriptive. The data used are secondary time series for the period of January 2014-December 2017 which has been published by the website of Bank Indonesia and Otoritas Jasa Keuangan (OJK). The method of analysis used is multiple linear regression. The results of this study indicate that the profit sharing rate, financing to deposit ratio and inflation rate significantly influence the number of mudharaba deposit accumulation. Variable of profit sharing rate have a positive relation to mudharaba deposit. However, the variable of financing to deposit ratio and inflation rate have a negative relation to mudharaba deposit.